2014
DOI: 10.1002/2014wr015506
|View full text |Cite
|
Sign up to set email alerts
|

Integration of altimetric lake levels and GRACE gravimetry over Africa: Inferences for terrestrial water storage change 2003–2011

Abstract: Terrestrial water storage (TWS) change for 2003-2011 is estimated over Africa from GRACE gravimetric data. The signatures from change in water of the major lakes are removed by utilizing kernel functions with lake heights recovered from retracked ENVISAT satellite altimetry. In addition, the contribution of gravimetric change due to soil moisture and biomass is removed from the total GRACE signal by utilizing the GLDAS land surface model. The residual TWS time series, namely groundwater and the surface waters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…Estimations of X Surface water can be introduced by converting altimetry measurements to storage following, e.g., Moore and Williams (2014). Groundwater (X Groundwater ) estimation is missing in land surface models such as GLDAS and therefore is estimated here after solving the inversion.…”
Section: Filtering Of Lsm Storage Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimations of X Surface water can be introduced by converting altimetry measurements to storage following, e.g., Moore and Williams (2014). Groundwater (X Groundwater ) estimation is missing in land surface models such as GLDAS and therefore is estimated here after solving the inversion.…”
Section: Filtering Of Lsm Storage Simulationsmentioning
confidence: 99%
“…3.4) over a box 29°-63°E and 24°-43°N (that includes the seven basins), covering the period 2003-2013. Information on the surface water compartment is obtained by converting altimetry measurements over the Caspian Sea, Persian and Oman Gulfs, Lake Urmia (37 42 0 N 45 19 0 E), and Lake Tharthar (33 58 0 N 43 11 0 E) to storage changes following Moore and Williams (2014). All altimetry measurements are downloaded from (http://www.pecad.fas.…”
Section: Inverted Soil and Groundwater Storage Changesmentioning
confidence: 99%
“…GRACE estimates have been used to study long-term TWS changes at both global and regional scales [9][10][11][12][13][14]. For example, Humphrey et al [12] investigated the relative importance of linear trend and nonlinear interannual variability in long-term TWS changes throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Awange et al [9] found out that a catchment area of 4 × 4 • including Lake Naivasha in East Africa lost water at a rate of 1.4 cm/year for the period of 2002-2010. Ahmed et al [11] and Moore and Williams [13] found that large sectors of Africa are undergoing significant TWS variations (+44 mm/year to −15 mm/year) due to natural and anthropogenic causes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation